Elementary School Science Skills Practical Digital Teaching Module - Pratiwi, Ni Kadek Anggi; I.N Laba Jayanta (Universitas Pendidikan Ganesha, 2023)
There is no digital teaching module used in the learning process of elementary science skills to be able to train the ability to learn independently. This research aims to create a valid and practical digital teaching module for elementary school science skills development practice. The research model used is the ADDIE research model. The subjects of this research were 6 experts and 2 practitioners to determine the validity and practicality of the digital module being developed. The object of this research is the validity and practicality of the teaching module. The data collection method used is the questionnaire method. This development research used two data analysis techniques, namely qualitative descriptive analysis techniques and quantitative descriptive analysis techniques. Based on the validity and practicality test analysis, the digital teaching module practice for developing elementary science skills obtained validity from learning material experts at 96.6%, learning design experts at 91.3%, learning media experts at 95.56%, the results of practicality assessments from practitioners of 96%, the practicality assessment in the individual test was 93.3%, and the practicality assessment in the small group test was 95.56%, overall with very good qualifications. The research conclusions of the digital teaching module practice for developing elementary school science skills were declared valid and practical with very good qualifications. This research implies that students can more easily carry out practicums and can learn independently.